وقف تنفيذ القرار الإداري بين التشريع الجزائري و الفرنسي - عادل, بن عبد الله; داودي, حسام الدين (Sciences humaines, 2014)
إن المشرع الجزائري  منح الإدارة امتياز في تنفيذ قراراتها، استنادا إلى قاعدة الامتياز السابق(السير الحسن للمرفق العام) باعتبارها الوسيلة الأكثر فعالية، وهي المخولة قانونيا لحماية المصلحة العامة-الإدارة-، ورغم هذا الاستثناء في مواجهة الأفراد إلا أن الإدارة تظل مقيدة بشرط المشروعية، إذ كرس القضاء الإداري لحماية هذا المبدء وسائل قانونية عدة نذكرمنها دعوى الالغاء ، لكنها بدورها لا توقف تنفيذ القرار هذا ما حذى بالمشرع للجوء الى خلق الية جديدة وهي دعوى وقف التنفيذ، نظرا لما تمثله من ضمانات لحقوق الأفراد وحرياتهم في مواجهة الإدارة.   The Algerian legislation provided the administration with the privilege to execute its decisions based on the previous privilege rule (the good conduct of the public facilities) considering them as the most effective and which is entitled to protect the administration. Despite that execution in confronting individuals, the administration is still restricted with the legitimacy constraint. However, the administrative judiciary devoted legal means such as cancellation procedure to protect this principle. Though, it does not prevent the execution of that decision, what obliged the legislator to create a new mechanism which is execution cessation procedure that represents insurance of individual rights and freedom to confront administration.